2013
DOI: 10.1038/bjc.2013.508
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of inflammatory cell infiltration in colorectal cancer

Abstract: Background:Higher-grade inflammatory infiltrate is a promising marker for better prognosis in colorectal cancer (CRC). However, the knowledge on the interrelationships between different inflammatory cells and classifications is fragmentary.Methods:We analysed the densities of eight types of inflammatory cells in a prospectively recruited group of 117 CRC patients and determined their interrelationships and contributions to Klintrup–Mäkinen (K–M) score of overall peritumoural inflammation. We characterised the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
135
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 40 publications
11
135
2
4
Order By: Relevance
“…Moreover, the degree of inflammatory infiltration was negatively correlated with the the presence of lymph node metastasis, its size, exceeding the lymph pouches and infiltration structures near to metastatic lymph nodes. Our results are consistent with the observations of Galon et al (12), Menon et al (24) and Väyrynen et al (25). They confirmed that patients with high TNM stage linked with presence of distant metastases were correlated with lower immune response.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the degree of inflammatory infiltration was negatively correlated with the the presence of lymph node metastasis, its size, exceeding the lymph pouches and infiltration structures near to metastatic lymph nodes. Our results are consistent with the observations of Galon et al (12), Menon et al (24) and Väyrynen et al (25). They confirmed that patients with high TNM stage linked with presence of distant metastases were correlated with lower immune response.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found a negative correlation between serum endostatin levels and the numbers of mast cells and immature DCs in tumour stroma and mature DCs at the invasive front. Our earlier study (Väyrynen et al, 2013) showed that CD1a þ immature DC and mast cell counts, unlike T cell and CD83 þ mature DC counts, do not associate with stage, and these two cell types clustered far apart from other inflammatory cells in the hierarchical clustering, suggesting that these cell types are less relevant in tumourassociated immune responses. Instead, it has been reported that immature DCs and especially mast cells promote angiogenesis in certain conditions (Huang et al, 1994;Maltby et al, 2009;Fainaru et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…Immunohistochemical analyses of collagen XVIII (rabbit polyclonal antibody QH48) and inflammatory cell markers were carried out on formalin-fixed paraffin-embedded 3.5-mm sections as described earlier (Saarela et al, 1998;Väyrynen et al, 2013). The inflammatory cell markers used in this study were CD3 (T cells), CD8 (cytotoxic T cells), FoxP3 (regulatory T cells), CD68 (monocyte-macrophage lineage cells), neutrophil elastase (neutrophilic granulocytes), mast cell tryptase (mast cells), CD83 (mature dendritic cells (DCs)) and CD1a (immature DCs) (Väyrynen et al, 2013). Bound antibodies were detected using peroxidase-based EnVision kit (Dako, Copenhagen, Denmark).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anomalous phenotype of the tumour can encourage an infl ow of infl ammatory lymphocytes into tissues around the tumour. This ability of the immune system to function as a prime defence against cancer, to respond, recognise and eradicate any emerging or established tumour areas, acts as an indication of the aggressiveness of the tumour and also as a predictor for disease outcomes (Klintrup et al, 2005;V ä yrynen et al, 2013). Different types of immune cells infi ltrate the tumour microenvironment, comprising cells of both the innate and adaptive immune system.…”
Section: Introductionmentioning
confidence: 99%